Inhibition of HIV-1 Infection in Ex Vivo Cervical Tissue Model of Human Vagina by Palmitic Acid; Implications for a Microbicide Development - Lin, Xudong (Public Library of Science, 2011)
BACKGROUND: Approximately 80% of all new HIV-1 infections are acquired through sexual contact. Currently, there is no clinically approved microbicide, indicating a clear and urgent therapeutic need. We recently reported that palmitic acid (PA) is a novel and specific inhibitor of HIV-1 fusion and entry. Mechanistically, PA inhibits HIV-1 infection by binding to a novel pocket on the CD4 receptor and blocks efficient gp120-to-CD4 attachment. Here, we wanted to assess the ability of PA to inhibit HIV-1 infection in cervical tissue ex vivo model of human vagina, and determine its effect on Lactobacillus (L) species of probiotic vaginal flora. PRINCIPAL FINDINGS: Our results show that treatment with 100–200 µM PA inhibited HIV-1 infection in cervical tissue by up to 50%, and this treatment was not toxic to the tissue or to L. crispatus and jensenii species of vaginal flora. In vitro, in a cell free system that is independent of in vivo cell associated CD4 receptor; we determined inhibition constant (Ki) to be ∼2.53 µM. SIGNIFICANCE: These results demonstrate utility of PA as a model molecule for further preclinical development of a safe and potent HIV-1 entry microbicide inhibitor.